Patterns of individual coping, engagement with social supports and use of formal services among a five-country sample of resilient youth (2015)
ABSTRACT: Background. Although resilience among victims of child abuse is commonly understood as a process of interaction between individuals and their environments, there have been very few studies of how children’s individual coping strategies, social supports and formal services combine to promote well-being. Method. For this study, we conducted a multi-phase analysis of a qualitative dataset of 608 interviews with young people from five countries using grounded theory strategies to build a substantive theory of young people’s service and support use patterns. We started with an analysis of ten interviews (two from each country) and then compared these findings to patterns found in each country’s full dataset. Results. The substantive theory that emerged explains young people’s transience between individual coping strategies (cognitive and behavioral), reliance on social supports (family members, peers and teachers), and engagement with formal service providers whose roles are to provide interventions and case management. Young people’s patterns of navigation were shown to be contingent upon the individual’s risk exposure, his or her individual capacity to cope, and the quality of the formal and informal supports and services that are available and accessible. Conclusion. Differing amounts of formal resources in low-, middle- and high-income countries influence patterns of service use. Implications for better coordination between formal mental health services and social supports are discussed.